Hubungan Indeks Massa Tubuh terhadap Volume Oksigen Maksimal (VO2max) Mahasiswa Tingkat Pertama Fakultas Kedokteran Universitas Lampung - Salma Khairunnisa; Dewi Nur Fiana; Helmi Ismunandar; Khairun Nisa Berawi (Medula, 2023)
Maximum oxygen volume (VO2max) is the maximum oxygen uptake during exercise. People with good fitness have higher VO2max value ​​and can perform activities more vigorously than those with poor fitness. Body mass index (BMI) is one of the body composition factors that affect VO2max. VO2max can be measured through various methods, one of which is the Balke test. This study aims to determine the relationship of body mass index to VO2max in the first grade students of the Faculty of Medicine, University of Lampung. This research is a correlative analytic study with a cross-sectional approach using primary data which was conducted in one meeting in November 2022. The data is obtained using measuring body mass index (BMI) first, and followed by measuring VO2max using the Balke test method. This study uses sample of 39 batch 2022 male students of the Faculty of Medicine, University of Lampung who have previously passed the inclusion and exclusion criterias. The result in this study indicates that there is a significant relationship between body mass index and VO2max in the first grade students of the Faculty of Medicine, University of Lampung. In this study, the p value is <0.001 and the correlation coefficient is -0.812, which means that there is a very strong negative correlation between variables. This negative correlation relationship indicates that the higher the body mass index (BMI) will result in lower individual VO2max values, and vice versa.